Beyond capitalist enclosure, commodification and alienation: Postcapitalist praxis as commons, social production and useful doing. (February 2020) - Chatterton, Paul; Pusey, Andre
This paper aims to further a geographical agenda through the concept of postcapitalism. We outline its contours across three terrains of transformation between capitalism and postcapitalism: creating commons against enclosure, socially useful production that counters commodification, and joyful doing that negates alienated work. Secondly, we explore how postcapitalism is mobilised with different inflections through three contemporary debates: community economies, post-work and autonomous perspectives. We then illuminate how one area of social practice (platform cooperatives) resonates with postcapitalist terrains and debates. We conclude by exploring the, as yet unclear and partially formed, social and spatial landscape of postcapitalism.